A new polyclad species associated with Bankia martensi (Bivalvia) from the South Pacific coast of Chile, and its taxonomic position within Euplanidae (Platyhelminthes, Ilyplanoidea) - Brusa, Francisco (2014)
We describe a new genus and a new species of Polycladida, Namyhplana henriettae (Platyhelminthes, Euplanidae), which lives associated with the tubes of the bivalve Bankia martensi in the fjords of the South Pacific Ocean in Chile. This species is characterized by a ribbon-like body, light brown colour, anterior region devoid of pigment, few eyes, no tentacles, pharynx in the anterior region of the body with few folds, independent gonopores anterior to the medial body line, seminal vesicle strongly muscularized, digitiform penian papilla oriented posteroanteriorly, a curled vagina, and a large Lang’s vesicle ventral to the intestine. A phylogenetic analysis of the Euplanidae, based on morphological characters, is presented. With the dataset used, the family Euplanidae does not seem to be a monophyletic group. The new species is closely related to Taenioplana teredini (also discussed here) which presents life-habit characteristics that are similar to those of the new species